2014
DOI: 10.15680/ijirset.2014.0310040
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organophosphate Pesticide Utilizing Alkaline Phosphatase Producing Polyextremophile Bacillus Flexus from Lake Ecosystem of North Gujarat, India

Abstract: ABSTRACT:The biodiversity of alkaline phosphatase (ALP) producing microbes from the lake ecosystem of the North Gujarat region was explored. Methyl Green dye and Phenolphthalein diphosphate supplemented MG-PDP medium screened ALP producing microbes as deep green stained cultures. The best ALP producing isolate was put through phenetic and genetic identification on the basis of morphology, biochemistry, physiology and 16S rRNA analysis. This best ALP producer proved to be catalase and oxidase positive, spore fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The obtained results demonstrated that the maximum ALP productivity was recorded at pH values of 9 and 10 (31.7 and 27.19 U L -1 , respectively), with a notable falling off in productivity of ALP for slightly acidic (pH 6.0), neutral (pH 7.0) and slightly alkaline (pH 8.0) conditions to activities of 6.64, 11.46, and 15.76 U L -1 , respectively. Bacillus paralicheniformis APSO thus is confirmed to have a strong preference for alkaline conditions for ALP production; this is in accordance with other published reports detailing the necessity of alkaline conditions (pH 8.0 and 9.0) to obtain the maximum production of ALP by Bacillus subtilis 16 , Bacillus licheniformis 15 , and Bacillus flexus 14 . Of the activated pre-cultured inoculum amounts studied (1%, 2%, 5%, and 10% of the total fermentation broth), the highest ALP productivities (70.4 and 61.84 U L -1 min -1 ) were recorded when 5% and 10% of the fermentation broth was activated pre-cultured inoculum, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results demonstrated that the maximum ALP productivity was recorded at pH values of 9 and 10 (31.7 and 27.19 U L -1 , respectively), with a notable falling off in productivity of ALP for slightly acidic (pH 6.0), neutral (pH 7.0) and slightly alkaline (pH 8.0) conditions to activities of 6.64, 11.46, and 15.76 U L -1 , respectively. Bacillus paralicheniformis APSO thus is confirmed to have a strong preference for alkaline conditions for ALP production; this is in accordance with other published reports detailing the necessity of alkaline conditions (pH 8.0 and 9.0) to obtain the maximum production of ALP by Bacillus subtilis 16 , Bacillus licheniformis 15 , and Bacillus flexus 14 . Of the activated pre-cultured inoculum amounts studied (1%, 2%, 5%, and 10% of the total fermentation broth), the highest ALP productivities (70.4 and 61.84 U L -1 min -1 ) were recorded when 5% and 10% of the fermentation broth was activated pre-cultured inoculum, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Twenty-five bacterial isolates were obtained from the enrichment isolation process in the primary exploration phase. To screen ALP-producing isolates from the obtained isolates, the plate agar media assay used an artificial substrate that yielded a colored product like the yellow color of the para-nitrophenol end product as a result of para-nitrophenyl phosphate (pNPP) cleavage and a deep-green color as a result of cleavage of phenolphthalein diphosphate tetrasodium salt (PDP) in presences of methyl green (MG) as an indicator dye, as detailed by Patel Falguni and others 14 for selecting phosphatase producers. Thus, the formation of deep-green/yellow-stained colonies indicated a positive production.…”
Section: Resultsmentioning
confidence: 99%